International evidence on stochastic and deterministic monetary neutrality - Antonio E. Noriega; Luis M. Soria; Ramón Velázquez (Banco de México, 2008)
We analyze the issue of the impact of multiple breaks on monetary neutrality results, using a long annual international data set. We empirically verify whether neutrality propositions remain addressable (and if so, whether they hold or not), when unit root tests are carried out allowing for multiple structural breaks in the long-run trend function of the variables. It is found that conclusions on neutrality are sensitive to the number and location of breaks. In order to interpret the evidence for structural breaks, we introduce a notion of deterministic monetary neutrality, which naturally arises in the absence of permanent stochastic shocks to the variables.
Keywords: C15; C32; E51; E52; 330; Deterministic and Stochastic Neutrality and Superneutrality of Money; Unit Roots; Structural Breaks; Resampling Methods; Neutralität des Geldes; Unit Root Test; Strukturbruch; Welt